Fotografi Mikro untuk Arkeologi (Metode Alternatif Perekaman Data Visual) - Taufiqurrahman Setiawan (Berkala Arkeologi Sangkhakala, 2010)
AbstractVisual data recording is one activity that must be performed on archaeological research as a supporting data description of data obtained. However, not all data can be easily documented. Sometimes, the data obtained are in a small size and must be documented with a micro camera which is not owned by any research institution. Therefore, an alternative method is needed to accommodate the limitation that is owned by the research institution.